HARAPAN ORANG TUA MEMASUKKAN ANAKNYA KE MDA HAQQUL YAKIN RW 01 DESA TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR - Irfan, Hizbul; Jas, Jasfar; ', Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Research it is based on the hope of the old admit their children to MDA. For the purpose of know the hope of the old admit their children to MDA Haqqul Yakin RW 01 Desa Tarai Bangun Kecamatan Tambang Kabupaten Kampar. Formulation problems in this research was how high the hope of the old admit their children to MDA Haqqul Yakin RW 01 Desa Tarai Bangun Kecamatan Tambang Kabupaten Kampar?. Technique the sample collection using a technique simple random sampling (the sample collection at random simple). Technique the data in this research was to technique chief, which consisted of 34 items statement.Data is collected of the respondents who consist of 20 people for a sample of testing and 104 people to the sample.After chief in testing, there are 8 items that invalid, and researchers dispose of all a statement that is not, so that the whole instrument expressed reliabel as alpha cronbach = 0,29. The results of the study be seen that the hope of the old admit their children MDA Haqqul Yakin RW 01 Desa Tarai Bangun Kecamatan Tambang Kabupaten Kampar are low.Seen of the scale interprestasi mean an average of 4,16.Based on the criteria and scale of interprestasi that has been set, so can be concluded that the hope of the old admit their children to MDA Haqqul Yakin RW 01 Desa Tarai Bangun Kecamatan Tambang Kabupaten Kampar were very low.Key words: The Hope Of The Old, The Hope Of The Old Admit Their Children To MDA